2022
DOI: 10.1186/s12943-022-01596-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals the genesis and heterogeneity of tumor microenvironment in pancreatic undifferentiated carcinoma with osteoclast-like giant-cells

Abstract: Background Undifferentiated carcinoma with osteoclast-like giant cells (OGCs) of pancreas (UCOGCP) is a rare subtype of pancreatic ductal adenocarcinoma (PDAC), which had poorly described histopathological and clinical features. Methods In this study, single-cell RNA sequencing (scRNA-seq) was used to profile the distinct tumor microenvironment of UCOGCP using samples obtained from one UCOGCP patient and three PDAC patients. Bioinformatic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…R package ‘monocle2’ was used for differentiation trajectory and pseudotime analysis of M2 macrophages ( Zhou et al, 2022 ). Subsequently, the ‘BEAM’ (branched expression analysis modeling) statistical algorithm was used to identify heterogeneous genes that play a key role in the differentiation of M2 macrophages ( Wang et al, 2022 ). R package ‘GSVA’ and ‘scMetabolism’ determined the enrichment of signaling pathways at the single-cell level ( Hanzelmann et al, 2013 ; Wu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…R package ‘monocle2’ was used for differentiation trajectory and pseudotime analysis of M2 macrophages ( Zhou et al, 2022 ). Subsequently, the ‘BEAM’ (branched expression analysis modeling) statistical algorithm was used to identify heterogeneous genes that play a key role in the differentiation of M2 macrophages ( Wang et al, 2022 ). R package ‘GSVA’ and ‘scMetabolism’ determined the enrichment of signaling pathways at the single-cell level ( Hanzelmann et al, 2013 ; Wu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) has been widely applied to dissect the cellular composition of tissues and explore functional heterogeneity. 21 , 22 , 23 It provides a convenient way to investigate how HERV expression varies among different cell types. Given that HERVs are dispersed in multiple copies throughout human genome, achieving accurate estimation of locus-specific expression of HERVs with scRNA-seq data is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…BLCA is one of the most common and most aggressive malignancies, the worried is that little progress has been made in the treatment of BLCA in the last few decades (Kimura et al, 2020;Lv et al, 2020). It is worth noticing that immunotherapy has shown great potential to treat MIBC and metastatic bladder cancer in the clinic (Nair et al, 2020;Pfail et al, 2021;Zhang et al, 2022). Previous studies have found that macrophages exert different effects on immunotherapeutic responses in advanced cancers (Petty and Yang, 2017;DeNardo and Ruffell, 2019;Zeng et al, 2020;Leblond et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment (TME) is constructed by interacting closely with the extracellular matrix (ECM) and stromal cells to evade detection and eradication by host immune surveillance ( Ge and Ding, 2020 ). Mounting studies have indicated the composition of the TME correlates strongly with immune response and chemotherapy, and regulations in various immune cells from the TME effect the clinical outcome of malignancies ( Erbani et al, 2022 ; Friedrich et al, 2022 ; Pang et al, 2022 ; Wang et al, 2022 ). Tumor-associated macrophages (TAM) drive tumor progression, metastasis, and therapeutic resistance ( Larroquette et al, 2022 )but heterogeneity is a considerable factor in macrophages ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%